Polyphenols individual identification an d evaluation of the ligaria anticancer activity cuneifolia (liga - liga) - Carlos Arenas Chávez (2019)
Ligaria cuneifolia (Liga-Liga) is useec in traditional medicine in our country to treat different health disorders . Information about its pharmacologic properties is limited. In order to study this vegetal species we prepared a methanilic extract and performed identification by high performance liquid chromatography couled to a Phenomenex column Luna C18 with UV detection at 280 and 320 nm using electrospray ionization (ESI). The mobile phase was A: Water/ acetic acid 98/2 (v/v) and B: water/ acetonytrile/ acetic acid 49.5/50/0.5 with a flow speed of 1mL/min in a gradient program . Plant extracts (0-100 mglinL) were incubated in cell lines corresoding to colon cancer (HCT-116), breast cancer (MDA-MB-231), prostate cancer (PC-3), Liver cancer (Hep - G2), skin cancer (A-375) and ovarian cancer (OVCAR-3).The total content of polyphenols showed a significant amount of bioactive compounds. ligaria showed an activity dependent on all canvcer lines. Methanolic extract was more active in colon cáncer lines (IC50 = 28.14 mg/ml). Different polyphenols were identified such as: quercetin, chiorogenic acid , elagic acid,and chlorogenic acid glycoside . Excellent linear correlations were observed for total polyphenols and total anticarcinogenic activity.